Phased gap-free genome assembly of octoploid cultivated strawberry illustrates the genetic and epigenetic divergence among subgenomes - Song, Yanhong; Peng, Yanling; Liu, Lifeng; Li, Gang; Zhao, Xia; Wang, Xu; Cao, Shuo; Muyle, Aline; Zhou, Yongfeng; Zhou, Houcheng (Horticulture research, 2024)
The genetic and epigenetic mechanisms underlying the coexistence and coordination of the four diverged subgenomes (ABCD) in octoploid strawberries (Fragaria × ananassa) remains poorly understood. In this study, we have assembled a haplotype-phased gap-free octoploid genome for the strawberry, which allowed us to uncover the sequence, structure, and epigenetic divergences among the subgenomes. The diploid progenitors of the octoploid strawberry, apart from subgenome A (Fragaria vesca), have been a subject of public controversy. Phylogenomic analyses revealed a close relationship between diploid species Fragaria iinumae and subgenomes B, C, and D. Subgenome A, closely related to F. vesca, retains the highest number of genes, exhibits the lowest content of transposable elements (TEs), experiences the strongest purifying selection, shows the lowest DNA methylation levels, and displays the highest expression level compared to the other three subgenomes. Transcriptome and DNA methylome analyses revealed that subgenome A-biased genes were enriched in fruit development biological processes. In contrast, although subgenomes B, C, and D contain equivalent amounts of repetitive sequences, they exhibit diverged methylation levels, particularly for TEs located near genes. Taken together, our findings provide valuable insights into the evolutionary patterns of subgenome structure, divergence and epigenetic dynamics in octoploid strawberries, which could be utilized in strawberry genetics and breeding research.